The Effect of Advertising, Exhibition and Event Marketing to Improve Awareness Awareness and its Impact on Intereststo Visit to Destination Religi Tour in Padang City (Case Study of Muslim Tourists from Malaysia) - Elfitra Desy Surya (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
From the data released by the Tourism Office of West Sumatera Province, it is seen that tourist visit to West Sumatera tend to decrease from year to year .. However, this decline has made the industry players and the Tourism Office in West Sumatra both provinci and regency. The city began to think of how efforts should be made to increase the interest of visiting Muslim tourists from Malaysia. Because the achievement of Malaysian tourists visit per year to West Sumatra as many as 60,000 people in 2017, has not been achieved, although it has been pushed by running the event "Visit Padang Halal Year 2017" Not reached the target of tourists visiting Malaysia is because allegedly awareness of tourists from Malaysia to destinations West Sumatra religious tourism has not been fully terpenetrasi. Because the pockets of Malaysian tourists who come to the city of Padang not only exist only in Kuala Lumpur, but also to other areas such as Selangor, Ipoh, Kedah, even to Kelantan and Negeri Sembilan. Problem formulation of this research is Does Advertising, Exhibition and Event have an effect on to Improving Consciousness of Tourists, Do Advertising, Exhibition and Event have an effect on to Improving Tourists Interest, Does Increasing Awareness of Tourists Affect Improvement of Visiting, Does Advertising, Exhibition and Event marketing have an effect on Increased Visiting Interest through Tourist Awareness.